MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI ERA DIGITAL - Suherman, Maman; Subandi, Subandi; Lestari, Rahayu Dwi; Muthia, Derifa Siti; Agustendra, Apen (STKIP Pesisir Selatan, 2025)
The rapid development of information technology in the digital era demands that teachers integrate technology into the learning process. This challenge not only requires technical skills but also a high level of work motivation. This study aims to describe and analyze the influence of the principal’s transformational leadership in enhancing teacher work motivation at SDN Rancaekek 05 in the digital era. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observations, and document analysis. Informants included the principal, teachers, and other educational staff. The findings reveal that the principal acts as a transformational leader through four key dimensions: setting an example and providing positive influence, delivering an inspiring vision, encouraging innovation in facing digital challenges, and attending to the individual needs and potential of teachers. Strategies implemented include technology training, teacher rewards, and open, participatory communication. This study highlights how transformational leadership can practically foster an adaptive work culture and enhance teachers’ professional motivation amid the challenges of the digital age, particularly in public elementary schools operating with limited resources.